Cash Management and Financial Performance of a Private Ltd Company: A Case Studies of Elgon Millers Ltd - Immaculate Khalayi (Uganda Christian University, 2024)
The study was designed to evaluate cash management and financial performance in Private ltd Company by assessing the relationship between the two variables. The research was aimed at achieving the following objectives; to find out the effect of Cash Collection and financial performance, to find out the effect of cash disbursement on financial performance, to find out the effect of cash budgeting and financial performance of Private Ltd Company. A case study design was adopted during the study; information was obtained from primary sources using questionnaires and interviews and purposive sampling was used. Finding: a positive significant relationship between cash collection and financial performance (r = 0.985**, p< 0.01), also cash disbursement and financial performance, a significant positive relationship was revealed from the results (r = 0.943**, p< 0.01), and finally findings revealed that there is a positive and significant relationship between cash budgeting and financial performance with a result of (r = 0.978**, p< 0.01). If cash management is purely monitored, it becomes easy to implement and plan for the profits to be generated by the firm and therefore it is only through effective implementation of cash management that firms get desired profit set levels therefore the researcher concluded that cash management has a positive effect on financial performance of organizations. Recommendations suggested included the need for deploying a cash management system which involves support and coordination among multiple departments, putting into place more controls to ensure that cash is safe and also using more of the accrual basis of cash out flow than the cash basis in order to maintain the liquidity at an optimal level.